Metal phosphates: new vistas for catalysed oxidations with hydrogen peroxide - Rocha, Graça Oliveira (1993)
Crystalline zirconium phosphates are potentially interesting as catalysts, since certain forms possess regular layer structures within which are strongly acidic sites which may undergo ion exchange with a range of metal cations. Hydrogen peroxide is particularly suitable to catalytic activation. Tetravalent metal phosphates, being highly insoluble and having strongly acidic sites, were therefore candidates for study as H2O2 catalysts.